PERBEDAAN KONSENTRASI ELEKTROLIT TERHADAP HASIL PENCELUPAN BAHAN SUTERA MENGGUNAKAN EKSTRAK BUNGA KEMBANG SEPATU DENGAN MORDAN BELIMBING WULUH - Sari, Nicky Wulan; Ramainas, Ramainas; Adriani, Adriani (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The purpose of this research is to explain the different of electrolite concentrate of the result emmersion of slik by using exctract kembang sepatu flower with mordan belimbing wuluh is seen from the colour (hue), bright dark of the colour (value) and excitement of the colour. The kind of this research is experiment research. There are two variables of this research, first X variable is kembang sepatu flower that immerse of the silk, X1 variable is immerse to electrolite concentrate 10 gr, X2 is immerse to 60 gr and X3 is immerse to 120 gr electrolite concentrate. Both of variables Y is different immersion of the result from the name of colour (hue), bright dark of the colour (value) and excitement of the colour. The kind of the data are using primer data. The source of the data in this research is 15 of the participant. The analysis of technique of the data that used is one directionÂ of one direction. The processing of the data use to SPSS 16 program. From the result of the analyze data is about the name of the colour (hue) gething the same colour of immerse without using electrolite and each electrolite concentrate is soft red purple, using exctract kembang sepatu flower with mordan belimbing wuluh. The result of the analysis data bright dark of the colour (value) showed: Fhitung > Ftabel = 3,284 > 3,22 itâ€™s mean has the significant different with bright, dark of the colour (value) in excitement, the colour explain Fhitung < Ftabel = 0,613 < 3,22 mean that there is no different excitement of the colour of different electrolite concentrate in emmersion of silk by using extract kembang sepatu flower with mordan belimbing wuluh. Â Kata kunci: Perbedaan konsentrasi elektrolit, hasil pencelupan bahan sutera menggunakan ekstrak bunga kembang sepatu, mordan belimbing wuluh.